Broad diversity of Mycobacterium tuberculosis complex strains isolated from humans and cattle in Northern Algeria suggests a zoonotic transmission cycle - Damene, Hanane; Tahir, Djamel; Diels, Maren; Berber, Ali; Sahraoui, Naima; Rigouts, Leen (PLOS Neglected Tropical Diseases, 2020)
Author summary To establish the circulating genotypes causing human and bovine tuberculosis (TB) in Northern Algeria, spoligotyping was used to characterize 296 Mycobacterium tuberculosis complex isolates of human (n = 115) and bovine (n = 181) origin. Molecular identification showed that most human isolates were identified as M. tuberculosis, with few M. bovis isolates, while among cattle, M. bovis, M. caprae, “M. pinnipedii-like” and “M. microti-like” isolates were found. Among M. tuberculosis isolates, 84 (78.5%) were classified into six families, with three prevailing genotypes (Latin–American Mediterranean (LAM), T clade and Haarlem). Concerning M. bovis, three spoligotype profiles (SB0120, SB0121 and SB0134) were predominant in Algeria, as in other Northern African countries. In addition, we identified some new M. bovis types (SB2695 to SB2701). For the first time in Algeria, M. bovis was found in 6% of human cases analyzed in this study. Furthermore, we documented regional variability in the prevalence of bovine TB among slaughtered cattle and in the probability of human TB being caused by M. bovis, suggesting the zoonotic transmission of M. bovis. This finding should draw the attention of Algerian health authorities to the importance of the effective control of bovine TB, including the establishment of traceability systems for livestock from the farm to slaughterhouse and between farms.